Effect of activation energy on detonation re-initiation behaviors in hydrogen-air mixtures - Tang, S; Zhang, S; Lai, S; Xu, C; Fang, X (American Institute of Aeronautics and Astronautics, 2024)
Two-dimensional simulations of a detonation propagating over a semi-cylinder in a channel filled with a stoichiometric hydrogen-air mixture are presented. A full set of Navier-Stokes equations is solved using a third-order WENO algorithm with HLLC flux, coupled with a calibrated, single-step chemical diffusive model (CDM). Simulation results using five different effective activation energies $\mathcal{E}=$ 4, 6, 10, 12 and 14 are presented featuring four distinct detonation attenuation regimes, including unattenuated detonation transmission ($\mathcal{E}=$ 4), critical detonation re-initiation ($\mathcal{E}=$ 6, and 10), cycled detonation re-initiation ($\mathcal{E}=$ 12), and complete quenching ($\mathcal{E}=$ 14). The degree of cell irregularity and the intensity of triple points are found positively correlated with the effective activation energy. With a low effective activation energy ($\mathcal{E}=$ 4), the CDM captures a regular cellular pattern, and the cellular structure remains intact as it propagates over the obstacle. With intermediate effective activation energies ($\mathcal{E}=$ 6, and 10), the detonation cell size increases and the cell structures become less regular with emerging multi-level cell structures. Here, a critical detonation re-initiation event is captured, where a strong transverse detonation wave forms following the Mach shock reflection, and eventually leads to a steady detonation propagation. At high effective activation energy ($\mathcal{E}=$ 12), the initial transverse detonations fail to produce a self-sustained detonation wave and multiple ignition and quenching events are found before the final establishment of the detonation wave.